The Effects Of Implementation Of Survey Strategy, Question, Read, Recall, And Review (SQ3R) On The Ability Of Read The Understanding Of Students Of The 5th Grade Inpres 1 Rappocini City Of Makassar - Ayu Nurul Aisyah (International Journal of Elementary School Teacher, 2022)
Students reading comprehension skills are still lacking. Many students do not know content or meaning of the reading they have read. The main problem in this study is now to describe the implementation of the SQ3R strategy for fifth grade students of SD INPRES BTN IKIP 1, Rappocini District, Makassar City, how is the description of the results of reading comprehension skills for fifth graders of SD INPRES BTN IKIP 1, Rapocini District, Makassar City, and whether there is an effect on the implementation of the SQ3R stategy. On the reading comprehension skills of fifth graders of SD INPRES BTN IKIP 1, Rappocini District, Makassar City. This study aims to describe the implementation of the SQ3R strategy, to determine the description of students reading comprehension skills, and to determine the effect of implementing the SQ3R strategy on the reading skills of fifth grade students of SD INPRES BTN IKIP 1, Rappocini District, Makassar City. This type of research is an experimental (Quasi Experimental Design) with a quantitative approach. The population in this study were all fifth grade students. The sample in this study was 21 students in class V A and 21 students in class V B. The instrument used was a test of students reading comprehension skills (pre-test and post-test). Data Collection techniques in this study were observation, tests and documentation. After the data is collected then the processing is done by statistical analysis and inferential statistics with the help of IBM SPSS version 26.The results of the descriptive analysis showed that the average value of comprehension reading skills in the experimental class before using the SQ3R strategy (pre-test) was 60.71 in the poor category, while the average value of students after the implementation of the SQ3R strategy (post-test) was 84.76 in the good category. Furthermore, the average value of students reading comprehension skills in the control class that was not treated without applying the SQ3R strategy (pre-test) was 60.48 which was in the less category while the average value of not being treated without applying the SQ3R strategy (post-test) was 68.57 which was in the less category. Ststistical results using manual calculations of independent sample t-test with the help of the IBM SPSS Statistic Version 26 application. The  value is obtained with df (40) = 2.021 while  is 4.128,  (4.128)  > 2.021) so that H0 is rejected and H1 is accepted. Based on the results of the  study, there is a positive effect of implementing the SQ3R strategy on the reading comprehension skills of fifth graders of SD INPRES BTN IKIP 1, Rappocini District, Makassar City